1980
DOI: 10.1016/0300-483x(80)90056-6
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects of surfactants, IV. Effects of non-ionics and amphoterics on HeLa cells

Abstract: SUMMARYSurfactants, representing 3 non-ionic and 1 amphoteric series of homologs exhibited marked differences in their lethal and non-toxic effects on HeLa cells. Toxicity of non-ionics generally decreased inversely with increasing hydrophilic chain length and increased with increasing size of the lipophile. Lethal levels of the surfactants coincided with surface tension reduction of the media to 45 dynes cm-1 or below. Surface tensions of non-toxic concentrations were substantially higher than those for toxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…The Microtox bacteria may require a minimum surface tension to sustain light output (remain alive) in a similar manner to other types of organisms reported elsewhere; for example, lethal concentrations of surfactant coincide with an ST of 49 Ϯ 4 dynes/cm (ϭmN/m) for the freshwater coelenterate Hydra attenuata and the authors explain this as the level that probably disrupts the cell membranes [19]. For HeLa cells, lethal levels of surfactants coincided with surface tensions of 45 dynes/cm or below [20]. The cell-surfactant interaction for B16 melanoma cells is reported to be highly dependent on the CMC [21], where loss of cell viability occurs at surfactant concentrations below the CMC, but cell lysis only occurs at or near the CMC.…”
Section: Discussionmentioning
confidence: 64%
“…The Microtox bacteria may require a minimum surface tension to sustain light output (remain alive) in a similar manner to other types of organisms reported elsewhere; for example, lethal concentrations of surfactant coincide with an ST of 49 Ϯ 4 dynes/cm (ϭmN/m) for the freshwater coelenterate Hydra attenuata and the authors explain this as the level that probably disrupts the cell membranes [19]. For HeLa cells, lethal levels of surfactants coincided with surface tensions of 45 dynes/cm or below [20]. The cell-surfactant interaction for B16 melanoma cells is reported to be highly dependent on the CMC [21], where loss of cell viability occurs at surfactant concentrations below the CMC, but cell lysis only occurs at or near the CMC.…”
Section: Discussionmentioning
confidence: 64%
“…Ernst and Arditti [20] also indicated that physical properties of surfactants are a principal cause of the toxic effects of these detergents in HeLa cells. These researchers observed that the toxicity of nonionics generally decreased inversely with increasing hydrophilic chain length and increased with increasing size of the lipophile.…”
Section: Resultsmentioning
confidence: 99%
“…Proteins solutions emulsified in organic phase were doubleemulsified in aqueous phase to form a water-in-oil-in-water (W/O/W) emulsion or protein dispersed in organic solvents were emulsified in aqueous phase to form an oil-in-water emulsion (O/W) (4,5). Thus, various emulsifiers have been employed to stabilize the multiple interfaces between two immiscible solvents, such as PVA and Tween ® (nonionic polyoxyethylene surfactants), whose biocompatibility was not yet elucidated for in vivo applications (6,7). Therefore, several studies have been employing alternative strategies such as a melt dispersion method and an emulsifier-free emulsion method to eliminate or avoid the use of those surfactants for fabrication of microspheres (8,9).…”
Section: Introductionmentioning
confidence: 99%